Maskulinisasi Ikan Cupang (Betta splendens) Melalui Perendaman Larva Menggunakan Madu Hutan: Masculinization of Betta Fish (Betta splendens) Through Larval Immersion Using Forest Honey - Yunus, Heri Setiawan; Maulana, Fajar; Widarto, Tri Heru (Jurnal Sumberdaya Hayati, 2025)
Betta fish are freshwater species known for their territorial behavior and pronounced aggressiveness. The beauty of the color, shape and pattern of fish is special attraction so that it has high selling value, especially in males. Reversal sex through masculinization techniques, is able to produce higher study ratio. This study aims to test effectiveness of immersion betta fish (B. splendens) larval stage in honey solution and study its effect on fish survival. This study used complete randomized design (RAL) method with one factor in the form of immersion time. There were five lengths of immersion as treatment, 0 hours (Control), 24 hours (P1), 28 hours (P2), 32 hours (P3) and 36 hours (P4) with 3 tests each. Larvae used are aged 3 days after hatching. The results showed that length of soaking had a significant (P<0.05) on survival rates in all treatments. The percentage of male sex observed in the K treatment was 21.66±4.81%, P1 was 50.85±2.92%, P2 was 50.58±4.59%, P3 was 52.46±3.90% and P4 was 0%. The effective soaking time treatment is for 24 hours. The effect of natural honey on the masculinization of betta fish was effective in P1 treatment of 50.85±2.92% and survival rate of 94.95±1.37%.